Gastroprotective effects of water extract of domesticated Amauroderma rugosum against several gastric ulcer models in rats - Yanzhen Mai; Siyuan Xu; Ru Shen; Bairu Feng; Hong He; Yifei Xu (Taylor & Francis Group, 2022)
Context Amauroderma rugosum (Blume & T. Nees) Torrend (Ganodermataceae) is an edible mushroom with medicinal properties. However, the effects of A. rugosum on gastric ulcer remain unclear.Objective To investigate the gastroprotective efficacy of water extract of A. rugosum (WEA) on gastric ulcer.Materials and methods Sprague-Dawley rats were randomly grouped as control, model, lansoprazole and 200, 100 and 50 mg/kg of WEA. After pre-treatment for seven days, ethanol- and indomethacin-induced gastric ulcer models were established. The gastric ulcer and histopathology were investigated. Enzyme-linked immunosorbent assay (ELISA), quantitative polymerase chain reaction (Q-PCR) and Western blot assays were conducted to explore the potential anti-inflammatory effect and mechanism of WEA. Additionally, the pyloric ligation model was used to explore the influence of WEA on gastric acid and mucus.Results Pre-treatment with WEA (200, 100 and 50 mg/kg) effectively reduced ulcerous area in both ethanol-induced (71%, 88% and 71%) and indomethacin-induced (77%, 65% and 86%) gastric ulcer model. The gastric levels of tumour necrosis factor-alpha (TNF-α) (34% and 50 mg/kg), interleukin-6 (IL-6) (32% and 100 mg/kg) and interleukin-1β (IL-1β) (36%, 45% and 41%) were reduced significantly (p < 0.05) by WEA. Serum nitric oxide was decreased significantly (p < 0.05) at 200 and 50 mg/kg and PGE2 concentration was increased remarkably (p < 0.05) at 100 mg/kg. Gene expression of inflammasome Nlrp3, and the nuclear translocation of nuclear factor-κB (NF-κB) P65 were significantly decreased by WEA pre-treatment. However, the pH of gastric acid and secretion of mucus did not show any significant change.Conclusions The gastroprotective effect of WEA on gastric damage is attributed to anti-inflammation through the inhibition on NF-κB P65 nuclear migration and Nlrp3 gene expression.